Role of Neutrophil-Derived S100B in Acute Myocardial Infarction Patients From the Han Chinese Population - Cheng, Minghui; Su, Xu; Liu, Dan; Tian, Xiaoxiang; Yan, Chenghui; Zhang, Xiaolin; Han, Yaling (Frontiers in Cardiovascular Medicine, 2021)
Objective: The present study aimed to clarify the novel role of homeostatic calmodulin S100B and determine whether S100B genetic variants impact atherosclerosis progression in acute myocardial infarction (AMI). Methods: Plasma levels of S100B were measured systemically in AMI patients, stable angina pectoris, or control subjects. S100B coming from the human coronary artery thrombi obtained by the thrombectomy catheter was measured by immunohistochemical analysis, qRT-PCR and Western blot analysis. We also screened for S100B variations (rs9722, rs9984765, rs2839356, rs1051169 and rs2186358) through direct sequencing and investigated the relationship between these variants and AMI patients in the Chinese Han population. Results: S100B plasma levels increased significantly in AMI patients compared with stable angina pectoris patients and control subjects (117.56±65.57, 155.96±79.27, and 305.72±145. 31 pg/ml, respectively). S100B expression was increased in the neutrophils of coronary artery thrombi from AMI patients compared with the normal blood clot by immunohistochemical staining, and S100B expression was much obviously increased in fresh thrombi tissues than organised thrombi tissues. Western blot and qRT-PCR analysis displayed S100B expression increased in the coronary artery thrombi than the normal blood clot which was related to increased risk of AMI (OR=1.35, 95%CI: 1.12-1.65, P=0.02). After the neutrophils pretreated with siRAGE, S100B inducing the neutrophils migration were abolished through the NFκB–IL1β/IL6 signal pathway. Compared with their corresponding wild-type genotypes, S100B rs9722 variant were associated with increased susceptibility to AMI. Individuals with the S100B 9722 A allele had higher plasma S100B levels than those with the GG allele in both control and AMI participants (140.45±75.34 vs.107.06±58.46 and 348.46±156.15 vs.268.46±138.12 respectively). Conclusions: Neutrophil-derived S100B is a novel homeostatic calmodulin which is elevated in the early stages of myocardial infarction. The S100B rs9722 allele is independently associated with the occurrence of AMI in Chinese Han population, and the S100B rs9722 AA homozygote may promote the development of AMI.